The handbook of bank accounting : understanding and applying standards and regulations - Woelfel, Charles J. (Chicago : Bankers Pub. Co. ; Cambridge, England : Probus Pub. Co., 1993)
This book deals with bank accounting and regulation.
Includes bibliographical references (p. 395-401) and index.
rua 20/10/16
Ref.
Keywords: Banks and banking; Bank accounting; Bank regulation; United States